Legal Position of Buy Buck Guarantee Agreement in Guaranteeing Home Ownership Credit Facilities at PT. Bank Tabungan Negara, Sharia Branch, Kendari City - Alghifary, Dhio Alif Utama; Adillah, Siti Ummu (Jurnal Konstatering, 2025)
Abstract.This study aims to determine and analyze the legal position of the buy back guarantee agreement as collateral in home ownership credit at PT. Bank Tabungan Negara Cabang Syariah Kota Kendari, to determine and analyze the legal protection of users (customers) in the Buy Back Guarantee for down payments that have been paid to developers and credit installments that have been paid to the bank. The approach methods in this study are the statutory approach (Statue Approach), Conceptual Approach (Conceptual Approach), and Case Approach (Case Approach). This type of research is an empirical legal research. The types and sources of data in this study are primary data and secondary data which include primary legal materials, secondary legal materials and tertiary legal materials. The primary data collection method uses observation and interviews, for secondary data using document studies and literature studies. The data analysis method uses qualitative descriptive, using the theory of legal protection, the theory of legal certainty and the theory of justice. The results of the study indicate that the legal position of the buy back guarantee agreement as collateral in home ownership credit at PT. Bank Tabungan Negara Cabang Syariah Kota Kendari is the position of the buy back guarantee agreement as an accessoir agreement, namely pancillary agreements and their existence are intended to support the main agreement, so that if the main agreement is cancelled, the accessory agreement (liability rights) will also be cancelled. And the legal protection of users (customers) in the buy back guarantee for down payments that have been paid to the developer and credit installments that have been paid to the bank is the legal protection of users/customers in the buy back guarantee has not been legally protected because it has not been regulated in the legislation. Therefore, down payment payments to developers and credit installments to banks cannot be returned and become the risk of the user/debtor.Keywords: Agreement; BuyBack; Guarantee; Position.